2012
DOI: 10.1038/eye.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adherence to NICE Glaucoma Guidance in two different service delivery models

Abstract: Purpose To assess adherence patterns to the UK National Institute of Health and Clinical Excellence (NICE) guidelines on glaucoma management (2009) in a tertiary referral centre shared care setting and in a district general hospital (DGH) setting. Method We performed a retrospective case note analysis of 200 patients from two centres between January and June 2010. The two centres involved were a consultant-guided teaching hospital optometry-led shared care setting (setting 1) and a consultant-led DGH clinic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The authors’ previous study on university faculties and clinical residents had similar results 24. Since PubMed, MDConsult and TRIP have specific filters for guidelines, we recommend introducing these filters to practitioners and training them in order to facilitate ‘finding the best clinical practice guidelines’.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The authors’ previous study on university faculties and clinical residents had similar results 24. Since PubMed, MDConsult and TRIP have specific filters for guidelines, we recommend introducing these filters to practitioners and training them in order to facilitate ‘finding the best clinical practice guidelines’.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies also reported such a positive attitude towards clinical guidelines 10 23 40 41. A study in the UK shows that adherence to guidelines for initial assessment and choice of treatment and drug by ophthalmologists is good 24. However, the rate of guideline implementation in practice is not acceptable and, according to Ishii,42 there is a clinical gap between knowledge and practice.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that specialist optometrists, additionally trained in glaucoma, can make appropriate diagnostic and management decisions compared to a sub‐specialist ophthalmologist reference standard …”
Section: Resultsmentioning
confidence: 99%
“…With an established base of practices dispersed across the country, optometrists are well placed to redirect some eye care services away from acute hospitals, though there was also a high level of interest in hospital optometry positions. Under the UK's National Health Service (NHS), a number of innovative care pathways have emerged such as repeat measures, 25 referral refinement, 26 and optometry-led hospital-based glaucoma assessment clinics 27 for example, which involve optometrists in the co-management of glaucoma and have proven an effective strategy in dealing with increasing patient numbers.…”
Section: Discussionmentioning
confidence: 99%